Self-screening practice of breast cancer and associated factors among female students in Ethiopian universities using the theory of planned behavior: a cross sectional study - Wudneh Simegn; Abdulwase Mohammed Seid; Gashaw Sisay Chanie; Liknaw Workie Limenh; Lamrot Yohannes; Teshome Demelash Bitew; Dagnew Getnet Adugna; Mihret Melese; Fikrie Tegen Kassie; Wondim Ayenew (BMC Women's Health)
Abstract Background Breast cancer is the most common cancer among females. Assessing self-screening practices for breast cancer patients is vital for developing targeted interventions. The current study aimed to assess self-screening practices for breast cancer and associated factors via the theory of planned behavior constructs among female students in Ethiopian universities. Methods A cross-sectional study design was conducted using the theory of planned behavior constructs. The data were collected from January 30, 2022, to February 30, 2022, in Ethiopia. A structured, self-administered questionnaire was used. The validity and reliability tests were checked to use the questionnaire in the main study through a pilot test. The data were collected through online Google Forms by distributing them to university students via Telegram groups, Imo, emails, and Facebook. The collected data were exported to SPSS version 26 for analysis. Bivariate analysis was used to identify the candidate variables for multiple logistic regression (P value < 0.02). Those variables with a P value less than 0.05 were considered significant predictors of breast cancer screening practices. Results A total of 418 female students participated in the study. The respondents were aged between 18 and 37 years. In the current study, 318 (76.1%; 95% CI: 72.0, 80.4) university students had good screening practices for breast cancer. Nonhealth-related departments (AOR = 1.95; 95% CI: 1.11, 3.44), having training in breast cancer self-examination (AOR = 1.87; 95% CI: 1.04, 3.35), having a good attitude (AOR = 1.96; 95% CI: 1.11, 3.47), having good behavioral control (AOR = 4.1; 95% CI: 2.18, 7.71), and having good behavioral intentions (AOR = 1.88; 95% CI: 1.09, 3.24) were associated with self-screening practices for breast cancer patients. Conclusion Designing a theory of planned behavior-based educational interventions improve self-screening practices for breast cancer among university female students. These insights could guide the development of future breast cancer awareness and prevention programs in university settings, with the goal of increasing early detection rates and lowering the risk of breast cancer. The study also serves as foundational information for designing future research using more advanced study design methods.